2022
DOI: 10.1002/hyp.14685
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis in streamflow‐water table relation provides a new classification system of rainfall‐runoff events

Abstract: Rainfall-runoff event types can be used to better understand the hydrological functioning of catchments. In this study, we propose a framework to characterize and classify runoff events relying on the hysteresis analysis of the relation between streamflow (independent variable) and depth to water table (dependent variable). We evaluated hysteresis for 112 rainfall-runoff events occurred in the period 2012-2016 in a small forested catchment in the Italian Pre-Alps. Three main groups of rainfall-runoff events we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 59 publications
2
9
0
Order By: Relevance
“…Penna et al (2011) also observed clockwise (SM lagged discharge) and anticlockwise (discharge lagged SM) loops in an Alpine headwater catchment during dry and wet conditions, respectively. An analogous hysteresis loop inversion was also reported by Gelmini et al (2022) for discharge and water table dynamics in Ressi headwater catchment located at the foothills of the Central‐Eastern Alps. Similarly, studies conducted by Weill et al (2013) reported the dependence of discharge–storage hysteresis behaviour on mean saturation of the catchment and further development of the linear relationship between storage and discharge during higher degrees of saturation.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Penna et al (2011) also observed clockwise (SM lagged discharge) and anticlockwise (discharge lagged SM) loops in an Alpine headwater catchment during dry and wet conditions, respectively. An analogous hysteresis loop inversion was also reported by Gelmini et al (2022) for discharge and water table dynamics in Ressi headwater catchment located at the foothills of the Central‐Eastern Alps. Similarly, studies conducted by Weill et al (2013) reported the dependence of discharge–storage hysteresis behaviour on mean saturation of the catchment and further development of the linear relationship between storage and discharge during higher degrees of saturation.…”
Section: Introductionsupporting
confidence: 85%
“…The HI was well tested using various combinations of the field data collected from the Ressi, Alta Val de La Mare, and Bridge Creek catchments of Italy, in which the independent variable was discharge, and the dependent variables were SM, depth to the water table, electrical conductivity, and δ2H$$ {\delta}^2H $$. Gelmini et al (2022) also used Zuecco's HI to study streamflow and groundwater table relationships to classify rainfall‐runoff events in the Italian Pre‐Alps.…”
Section: Introductionmentioning
confidence: 99%
“…Whether the regional mechanism explaining the link between topography, water table, and flooding is dominated by saturation or infiltration processes (Blöschl, 2022) is an attractive question to follow this analysis. For instance, it could be addressed by looking into the shape of the evolving relationship between rain-fall, runoff, water table levels and flooded extent (e.g., Gelmini et al, 2022;Reager et al, 2014;Zuecco et al, 2016) at a regional level.…”
Section: Discussionmentioning
confidence: 99%
“…Where rainfall recharge is the driver of changes in groundwater levels and nitrate-nitrogen concentrations, 120 hysteresis analysis can be used to identify the lag between these two variables following a recharge event. While several hysteresis studies have considered the effect of near stream groundwater on stream-derived hysteresis curves, continuous high-frequency groundwater measurements have not been widely utilised (Aubert et al, 2013;Jacobs et al, 2018;Knapp et al, 2020;Winter et al, 2021;Gelmini et al, 2022).…”
Section: Continuous Uv Nitrate Sensors and High-resolution Data Analy...mentioning
confidence: 99%
“…In concentration-discharge studies the input of near stream groundwater is recognised (Knapp et al, 2020;Winter et al, 2021;Gelmini et al, 2022) but the timing and variation of groundwater solute discharges is source of nitrate-nitrogen, the timing of greatest surface water-groundwater connection (highest groundwater level) compared to highest nitrate-nitrogen concentration could be investigated. This study highlights that the nitrate-nitrogen concentration in groundwater can be just as varied as stream concentrations at the event scale 445 and is a valuable addition in understanding riverine hysteresis processes.…”
mentioning
confidence: 99%